Analisis literasi keuangan digital mahasiswa: Studi pada penggunaan mobile banking di Bank Syariah Indonesia - rahmawati, Indah putri (Maliki Interdisciplinary Journal, 2026)
This study explores the level of digital financial literacy among Islamic banking students at Universitas Islam Negeri Maulana Malik Ibrahim Malang, focusing on their use of Mobile Banking services provided by Bank Syariah Indonesia. The rapid digitalization of finance requires students not only to access technology but also to comprehend service features, transaction mechanisms, and technical risks inherent in Islamic digital banking systems. A descriptive qualitative approach was employed, with data collected through direct observation and literature review from institutional repositories. The findings indicate that although students have relatively high access to digital technology, their conceptual and practical understanding of Islamic contracts (akad) in digital form remains limited. This reveals a gap between technological availability and users’ readiness to internalize Islamic principles within digital practices. The study recommends the integration of a practice-oriented digital banking curriculum into academic programs. Such an initiative is expected to strengthen students’ digital financial literacy while promoting broader Islamic financial inclusion within academic environments. Consequently, students may act not only as users of Islamic banking technology but also as literacy agents who disseminate digital financial knowledge grounded in Islamic values to the wider community.